2006
DOI: 10.1073/pnas.0602216103
|View full text |Cite
|
Sign up to set email alerts
|

The putatively functional Mkrn1-p1 pseudogene is neither expressed nor imprinted, nor does it regulate its source gene in trans

Abstract: Here, we show that 5 Mkrn1-p1 is fully methylated on both alleles, a pattern indicative of silenced chromatin, and that Mkrn1-p1 is not transcribed and therefore cannot stabilize Mkrn1 transcripts in trans. A small, truncated, rodent-specific Mkrn1 transcript explains the product erroneously attributed to Mkrn1-p1. Additionally, Mkrn1 expression is not imprinted, and 5 Mkrn1 is fully unmethylated. Finally, mice in which Mkrn1 has been directly disrupted show none of the phenotypes attributed to a partial reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The 3.2-and 2.0-kb transcripts most likely encode rat MKRN1-long and -short, respectively. In testis, an additional smaller transcript of 0.75 kb was detected and presumably represents a further alternatively spliced MKRN1 mRNA encompassing exons 1-3 (49). PCR analysis with primers specific for MKRN1-long and -short cDNA, respectively, confirmed the presence of both variants in rat brain (Fig.…”
Section: Mkrn1 Ismentioning
confidence: 75%
“…The 3.2-and 2.0-kb transcripts most likely encode rat MKRN1-long and -short, respectively. In testis, an additional smaller transcript of 0.75 kb was detected and presumably represents a further alternatively spliced MKRN1 mRNA encompassing exons 1-3 (49). PCR analysis with primers specific for MKRN1-long and -short cDNA, respectively, confirmed the presence of both variants in rat brain (Fig.…”
Section: Mkrn1 Ismentioning
confidence: 75%
“…Reduction of Makorin-p1 RNA led to a drop in mRNA from the protein-coding gene and a significant disease phenotype in mice (Hirotsune et al 2003). This finding remains controversial, however, as a subsequent study showed that the pseudogene is, in fact, transcriptionally silent, and neither gene is imprinted (Gray et al 2006). Decreased production of high mobility group A1 (HMGA1) protein can lead to the deregulation of the insulin receptor (INSR) gene and subsequent development of type 2 diabetes mellitus (Brunetti et al 2001).…”
Section: Evidence For Pseudogene Functionmentioning
confidence: 93%
“…From these results Yano et al (2004) have proposed that the Makorin1-p1 RNA functions to stabilize the Makorin1 mRNA. However, a recent study by Nicholls and colleagues (Gray et al 2006) challenged the role of Makorin1-p1 in regulating Makorin1 mRNA stability. Gray et al (2006) provided evidence that both alleles of Makorin1-p1 in mice are hypermethylated and transcriptionally silent and therefore cannot stabilize the Makorin1 mRNA in trans.…”
Section: Pseudogene Transcripts: No More 'Junk'mentioning
confidence: 99%
“…However, a recent study by Nicholls and colleagues (Gray et al 2006) challenged the role of Makorin1-p1 in regulating Makorin1 mRNA stability. Gray et al (2006) provided evidence that both alleles of Makorin1-p1 in mice are hypermethylated and transcriptionally silent and therefore cannot stabilize the Makorin1 mRNA in trans. Furthermore, mice in which Makorin1 has been directly disrupted showed none of the phenotypes attributed to the partial reduction of Makorin1 (Gray et al 2006).…”
Section: Pseudogene Transcripts: No More 'Junk'mentioning
confidence: 99%